BCG‐trained innate immunity leads to fetal growth restriction by altering immune cell profile in the mouse developing placenta. Issue 5 (17th September 2021) - Dang, Yipu; Souchet, Camille; Moresi, Fabiana; Jeljeli, Mohamed; Raquillet, Bruno; Nicco, Carole; Chouzenoux, Sandrine; Lagoutte, Isabelle; Marcellin, Louis; Batteux, Frederic; Doridot, Ludivine
Abstract: Trained immunity is a new concept illustrating that innate immune cells are able to undergo a long‐term metabolic and epigenetic reprogramming after infection or vaccination, thus displaying either a pro‐ or an anti‐inflammatory phenotype during a sequential unrelated challenge. Innate immune cells such as natural killer (NK) cells and macrophages constitute a large part of the decidual leukocyte population at the maternal–fetal interface, playing an important role in placental development and as such in fetal growth and development. In this study, we hypothesized that training the innate immune cells before pregnancy could have an impact on pregnancy. To test this hypothesis, we used CBA/J x DBA/2 mouse model to investigate pregnancy outcomes and leukocyte population at the maternal–fetal interface. Although we were not able to show a beneficial effect of LPS‐tolerogenic training on fetal resorption, Bacillus Calmette–Guérin (BCG) training, known to prime innate immune cells to be proinflammatory, led to fetal growth restriction, without aggravating the fetal resorption rate. We also found that BCG training led to less NK cells and macrophages at the maternal–fetal interface at the early stage of placentation (E9.5), associated with a down‐regulation of Ccr3 and Lif mRNA expression. This induced altered leucocyte population profile can be an explanation for the subsequent fetal growth restriction. These data suggest that preconceptional infections‐induced trained immunity could influence pregnancy outcomes. Graphical Abstract: BCG immune training before pregnancy led to IUGR in mice by modifying immune cell frequency in the developing placenta, whereas LPS training had no effect